Body composition as an indicator of metabolic changes in mice obtained by in vitro fertilization - M. V. Anisimova; Yanli Gon; G. V. Kontsevaya; A. V. Romashchenko; N. V. Khotskin; A. K. Stanova; L. A. Gerlinskaya; M. P. Moshkin (Вавиловский журнал генетики и селекции)
To identify body systems subject to epigenetic transformation during in vitro fertilization (IVF), comparative morphological and functional studies were performed on sexually mature offspring of outbred CD1 mice, specific-pathogen-free (SPF), obtained by IVF (experiment) and natural conception (control). The studies included assessment of age-related changes in body weight and composition, energy intake and expenditure, and glucose homeostasis. To level the effects caused by the different number of newborns in the control and in the experiment, the size of the fed litters was halved in the control females. Males obtained using the IVF procedure were superior in body weight compared to control males in all age groups. As was shown by analysis of variance with experiment/control factors, gender, age (7, 10 and 20 weeks), the IVF procedure had a statistically significant and unidirectional effect on body composition. At the same time, IVF offspring outperformed control individuals in relative fat content, but were behind in terms of lean mass. The effect of the interaction of factors was not statistically significant. IVF offspring of both sexes had higher fat to lean mass ratios (FLR). Since adipose tissue contributes significantly less to total energy intake compared to muscle, the main component of lean mass, it is not surprising that at the same level of IVF locomotor activity offspring consumed less food than controls. When converted to one gram of body weight, this difference reached 19 %. One of the consequences of reduced utilization of IVF energy substrates by offspring is a decrease in their tolerance to glucose loading. The integral criterion for the effectiveness of restoring the initial glucose level is the area under the curve (AUC), the value of which was 2.5 (males) and 3.2 (females) times higher in IVF offspring compared to the corresponding control. Thus, the totality of our original and literature data shows an increase in the risk of metabolic disorders in IVF offspring, which is confirmed by epidemiological studies of a relatively young cohort of people born using assisted reproductive technologies.